Proposing Clinicopathological Staging and Mitotic Count as Prognostic Factors for Canine Soft Tissue Sarcomas - Cardoso de Almeida Moreira, Andrea Regina [UNESP]; Franzoni, Mayara Simão [UNESP]; dos Anjos, Denner Santos; César-Jark, Paulo; Nóbrega, Juliano [UNESP]; Laufer-Amorim, Renée [UNESP]; Valsecchi Henriques, Marina [UNESP]; Neto, Osmar Pinto; Fonseca-Alves, Carlos Eduardo [UNESP] (MDPI, 2023)
Soft tissue sarcomas (STSs) are a heterogeneous group of malignant mesenchymal tumors with similar histological features and biological behaviors. They are characterized by a low to moderate local recurrence rate and low metastasis, affecting approximately 20% of patients. Although this tumor set is vital in veterinary medicine, no previous unified staging system or mitotic count has been associated with patient prognosis. Therefore, this study proposed a new clinicopathological staging method and evaluated a cut-off value for mitosis related to the survival of dogs affected by STS. This study included 105 dogs affected by STS, treated only with surgery, and a complete follow-up evaluation. The new clinicopathological staging system evaluated tumor size (T), nodal involvement (N), distant metastasis (M), and histological grading criteria (G) to categorize the tumor stage into four groups (stages I, II, III, and IV). The proposed tumor staging system was able to differentiate patients’ prognoses, with dogs with stage IV disease experiencing the lowest survival time and dogs with stage I disease having the highest survival time (p < 0.001). Moreover, we assessed the median mitosis (based on mitotic count) and its association with overall survival. Our study’s median mitosis was 5, and patients with ≤5 mitoses had a higher survival time (p = 0.006). Overall, the proposed staging system and mitotic count seemed promising in the prediction of patient prognosis.
Keywords: canine; mesenchymal tissues; overall survival; sarcomas